Mieke Bal: Recreating Old Times - Carreño Rio, Rodrigo (Eikón / Imago, 2019)
Mieke Bal (theorist and art historian) is known for her studies where she is in a constant trip which freshen the contemporary art. Along her career, she has renewed, through reinterpretation, terms such as space, temporality or movement as displacement and time – key concepts in her theories. But if she has stood out for something, it is always linked to visual studies. She advocates that the images are more than just a physical element; they are different ways of getting in front of the audience. All her studies have been displayed at Emma & Edvard exhibition: Love in the Time of Loneliness; Bal was the exhibition coordinator at The Munch Museum, from January the 27th to April the 17th, 2017. She created new elements for this exhibition through new demonstrative ways.